Mandible fractures and dental injuries related to road traffic accidents over a 12‐year period—Retrospective multicentre study. Issue 2 (25th November 2020) - Nogami, Shinnosuke; Yamauchi, Kensuke; Morishima, Hiromitsu; Otake, Yoshio; Kouketsu, Atsumu; Higuchi, Keisuke; Hirotani, Hiroaki; Kumagai, Masahiro; Takahashi, Tetsu
Abstract: Background/Aim: Road traffic accidents (RTAs) are a common cause of maxillofacial injuries. The aim of this retrospective multicentre study was to investigate the characteristics of maxillofacial fractures and dental injuries that occurred in RTAs in Miyagi, Japan. Materials and Methods: The records of 404 patients with maxillofacial injuries treated at the Oral and Maxillofacial Surgery Departments of four different institutions over a period of 12 years were analysed. Ninety‐nine of these patients had suffered these injuries in an RTA. RTA‐related cases were divided according to age, gender, presentation month, presentation day of the week, transportation mode, time of accident, fracture sites and fracture mechanism. Results: There were 72 males and 27 females who suffered injuries as the result of an RTA, for a male‐to‐female ratio of 2.7:1.0, with a mean age of 35.3 years (range, 1‐86 years old). Most of the accidents occurred in June and on a Wednesday, and most of the affected patients were riding a bicycle at the time. The number of patients with maxillofacial injuries related to bicycle riding showed an increasing trend in recent years. Mandible fractures were the most prevalent, followed by dental injuries and maxilla fractures. In cases with a single fracture of the mandible, the symphysis was the most frequent site, while in those with multiple fractures, the association of symphysis and bi‐lateral condyle fractures was the greatest. For bicycle‐related accidents, a single fracture in the mandible occurred more often than multiple fractures. Conclusions: The number of RTA‐related injuries while bicycle riding showed an increasing trend with mandible fractures commonly seen in those cases. Efforts to reduce maxillofacial injuries related to bicycle accidents are needed.